(untitled) (Medical Forum Monthly, 2024)
Objective: The study was designed to determine frequency of clinical manifestations, associated risk factors and early diagnosis to avoid complications in cases of liver abscess in hospital based study. Study Design: Descriptive study Place and Duration of Study: This study was conducted in the Medical Unit, Bolan Medical Complex Hospital, Quetta, Pakistan from August 2006 to Feb: 2008. Materials and Methods: 100 consecutive cases of liver abscess were reviewed. 99 cases (99%) were amoebic and 01 (1%) gynogenic. Majority of liver abscess were single and in right lobe (92%). Four (04%) in left lobe and four (04%) in both lobes. Results: Ultrasound guided aspiration with metronidizole was performed in 35% of our patients. These patients had abscess that were usually larger then 5cm in diameter. The other cases were managed initially empirically with parentral antibiotics then with oral antibiotics. We found that percutaneous aspiration of liver abscess is helpful to confirm diagnosis provides the a better bacteriological culture yield, gives a good outcome and may uncover clinically unsuspected conditions like malignancy and tuberculomas which may mimic the presentation of liver abscess. Conclusion: We recommend that ultrasound guided aspiration is a safe, economical easy way of management of liver abscess with low morbidity and negligible mortality.